Characteristics of youth who leave the emergency department without being seen following sports-related concussion - Jacquelyn J Deichman‡; Janessa M Graves‡; Tracy A Klein; Jessica L Mackelprang (Concussion)
Aim: Despite the rising incidence of emergency department (ED) visits for sports-related concussion, the frequency and characteristics of youth leaving before being seen are unknown. Methodology: N...